The Relationship between Mother’s Education and the Intensity of Gadget Use - Wenda Amalia Rizky; Siti Arifah (GLOBAL HEALTH SCIENCE GROUP, 2026)
The rapid growth of digital technology has influenced the behavior of toddlers, including the increasing use of gadgets from an early age. This study aimed to determine the relationship between parents’ educational level and gadget use among toddlers in Gatak Village, Klaten. This research employed a quantitative method with a correlational cross-sectional design. A total of 69 respondents were selected using purposive sampling based on inclusion criteria of parents with children aged 1–3 years. Data was collected through questionnaires assessing parental education level and the frequency of gadget use by children, the questionnaires had been tested for validity and reliability. The validity test yielded correlation coefficients ranging from 0.726 to 0.876, while the reliability test using Cronbach’s Alpha produced a value of 0.742, indicating that the instrument was both valid and reliable. The results showed that most parents had a high school education (44.9%) and that children’s gadget use was mainly at a low level (47.8%), with a p-value of 0.167, indicating no significant relationship p between parental education level and children’s gadget use. It can be concluded that formal education does not directly influence gadget use intensity among toddlers; instead, parental supervision and digital literacy play more essential roles.